Towards The Deep Semantic Learning Machine Neuroevolution Algorithm: An exploration on the CIFAR-10 problem task - Hofman, Olivier Jean Marie (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics